“No beast so fierce but knows some touch of pity”: Compassion and the Nonhuman in Richard III - Anne Sophie Refskou (Multicultural Shakespeare, 2021)
When Lady Anne accuses Richard of cruelty in the wooing scene of act one in Richard III, she claims that even the fiercest beast will demonstrate some degree of pity. Her attempt to categorize Richard as somehow both less than human and less than a beast, however, leaves her vulnerable to Richard’s pithy retort that he knows no pity “and therefore [is] no beast” (1:2:71-2). The dialogue swiftly moves on, but the relation between the emotional phenomenon known as pity or compassion and the nonhuman, briefly raised in these two lines, remains unresolved. Recent scholarship at the intersection of early modern studies, historical animal studies and posthumanism has demonstrated ways in which the human-animal binary is often less than clearly articulated in the sixteenth and seventeenth centuries. Building on such work, and adding perspectives from the history of the emotions, I look closely at the exchange between Anne and Richard as characteristic of pre-Cartesian confusion about the emotional disposition—in particular compassion—of animals. I argue that such confusion can in fact be traced throughout Richard III and elsewhere in the Shakespeare canon and that paying attention to it unsettles the more familiar notion of compassion as a human species distinction and offers a new way to read the early modern nonhuman.